Enhanced Galvanic Corrosion Phenomenon in the Welded Joint of NiCrMoV Steel by Low-Cycle Fatigue Behavior. Issue 12 (1st January 2019) - Weng, S.; Huang, Y. H.; Xuan, F. Z.; Zheng, S. L.
Abstract : The effect of microstructural changes on the corrosion of a NiCrMoV steel welded joint induced by low-cycle fatigue behavior in chloride solution has been investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), potentiodynamic polarization curve tests and scanning vibrating electrode technique (SVET) tests. During the low-cycle fatigue tests, cyclic softening takes place in the three zones (base metal, BM/weld metal, WM/heat affected zone, HAZ) of the welded joint due to the decrease of dislocation density or the formation of low-energy structures. Compared to the as-received specimens, the corrosion potential of each zone in the low-cycle fatigue damage specimens moves to the positive direction and the corrosion current density decreases. The corrosion resistance of the individual zone increases, which is related to the reduction of dislocation density or the formation of low-energy structures. However, the difference of corrosion potential between base metal and weld metal in the low-cycle fatigue welded joints becomes lager, which means that the galvanic corrosion susceptibility of the low-cycle fatigue welded joint increases. This may be caused by the difference of microstructural changes in the various regions of welded joints during cyclic plastic deformation.